In-situ synthesis of Ag/SBA-15 nanocomposites by the "pH- adjusting" method - Zhang, X.; Qu, Z.; Li, Xin Yong; Zhao, Q.; Zhang, X.; Quan, X. (2011)
Ag nanoparticles were incorporated into the channels of mesoporous SBA-15 by the "pH-adjusting" method. In this procedure, the pH value of the solution was adjusted up to 7.5 by adding ammonia. The structural properties of Ag/SBA-15 nanocomposites were systematically investigated by X-ray powder diffraction (XRD), Transmission electron microscope (TEM), N2 adsorption-desorption isotherms, inductively coupled plasma atomic emission spectroscopy (ICP-AES) and Fourier transform infrared spectroscopy (FT-IR) techniques. The characterization results reveal that the synthesized materials exhibit highly ordered hexagonal mesoporous structures, and highly dispersed Ag nanoparticles are confined inside the mesopores. It is the first time to report such high Ag loading on oxides fabricated by in-situ pH-adjusting method. © 2011 Elsevier B.V. All rights reserved.